Impact of Financial Technology Firms on Banking Performance: Insights from Indonesia - amal, Muhammad ahsanul; Fahmi, Noor Ali; Muhsin, An'nissa Miftahusnika Islami; Yustika, Baiq Reka; Shabur, Usman (Journal of Economics, Bussiness and Management Issues, 2024)
The presence of fintech companies in the banking sector of Indonesia plays a crucial role in enhancing the conventional financial system. This study examines the influence of financial technology (Fintech) firms on the performance of banks by utilizing data from the Indonesian banking sector between 2018 and 2022. This study employs a regression analysis using a data panel fixed effect model. This study quantifies the impact of different financial variables, including Capital Adequacy Ratio (CAR), Gross Non-Performing Loans (NPL), Net Interest Margin (NIM), Return On Assets (ROA), Return On Equity (ROE), Operating Expense to Operating Income (BOPO), and Loans. Control factors in the context of Fintech include the deposit ratio (LDR), gross domestic product (GDP), and inflation. The results indicate that the financial indicators, including CAR, NPLgross, ROA, ROE, and NIM, do not have a statistically significant influence on Fintech. Additionally, Fintech is significantly influenced by other indicators such as BOPO (Balance of Payments) and LDR (Loan-to-Deposit Ratio), as well as control variables, including GDP (Gross Domestic Product) and inflation. This demonstrates that Indonesian banks can reap advantages by engaging in partnerships with fintech startups to enhance the financial system and optimize corporate profitability resulting from this collaboration.